National point prevalence study on carriage of multidrug-resistant microorganisms in Dutch long-term care facilities in 2018. (10th March 2021) - van Kleef, Esther; Wielders, Cornelia C H; Schouls, Leo M; Feenstra, Sabiena G; Hertogh, Cees M P M; Bonten, Marc J M; van Weert, Yolanda; Tostmann, Alma; van der Lubben, Mariken; de Greeff, Sabine C; ,
Abstract: Objectives: Long-term care facilities (LTCFs) may act as a reservoir of ESBL-producing Enterobacterales (ESBL-E) and carbapenemase-producing Enterobacterales (CPE) for hospitals and the general population. In this study, we estimated the prevalence and molecular epidemiology of rectal carriage with ESBL-E and CPE in residents of Dutch LTCFs between March 2018 and December 2018. Methods: LTCFs were geographically selected across the country. For each LTCF, a random sample of residents were tested for ESBL-E and CPE in 2018. To identify risk factors for high carriage prevalence and/or individual carriage, characteristics of LTCFs and of a subset of the tested residents were collected. WGS was conducted on isolates from LTCFs with an ESBL-E prevalence of >10% and all CPE isolates to identify institutional clonal transmission. Results: A total of 4420 residents of 159 LTCFs were included. The weighted mean ESBL-E prevalence was 8.3% (95% CI: 6.8–10.0) and no CPE were found. In 53 LTCFs (33%), where ESBL-E prevalence was >10%, MLST using WGS (wgMLST) was performed. This included 264 isolates, the majority being Escherichia coli ( n  = 224) followed by Klebsiella pneumoniae ( n  = 30). Genetic clusters were identified in more than half (30/53; 57%) of high ESBL-positive LTCFs. Among the E. coli isolates, bla CTX-M-15 (92/224; 41%) and bla CTX-M-27 (40/224; 18%) were the most prevalent ESBL-encoding genes. For K. pneumoniae isolates, the most common was bla CTX-M-15 (23/30; 80%). Conclusions: The estimated prevalence of ESBL-E rectal carriage in Dutch LTCFs is 8.3% and resistance is observed mainly in E. coli with predominance of bla CTX-M-15 and bla CTX-M-27 . ESBL-E prevalence in LTCFs seems comparable to previously reported prevalence in hospitals and the general population.